MAKING DEMOCRACY WORK : INSTITUTIONAL REFORMS FOR MALAYSIA - Ooi, Kok Hin (Strategic Information and Research Development Centre, 2022)
"For decades, institutions have been deprived of the capability to provide meaningful and effective check and balance on the executive. However, following the end of dominant party rule in 2018 and the political turbulence that followed, the concentration of power in the prime minister began to be contested as the demand for reforms grew. In Making Democracy Work, Bersih brings together contributions from researchers and experts to study and propose recommendations in four key areas: electoral reforms, parliamentary reforms, public office appointments, and political finance. After the 'Sheraton Move' that led to the collapse of the Pakatan Harapan federal government and seven state governments during a global pandemic, Bersih commissioned a series of research reports to address political instability and the interconnected 'carrots' and 'sticks' contributing to party-hopping. This book is an abridged version compiling some of the reports. This edited volume offers insight to all who share a common interest in making Malaysia a strong, stable and mature democracy"--Back cover